A spectroscopic study and the effect of gamma rays on the stability and efficiency of boron subphthalocyanine dye for solar energy applications. (July 2023) - Alsufyani, Sultan J.; Alharbi, Abdulaziz N.; Atta, A.A.; Altalhi, Tariq A.; Refat, Moamen S.; Alkathiri, Ali A.; Ashour, Ahmed; Hassanien, A.M.
Abstract: Gamma irradiation with different doses (0.0, 10, 20, 30, 40 and 50 kGy) effects on the structural and optical features of organic boron subphthalocyanine (SubPc-Cl) thin films are studied. The main characteristic peaks and stability of SubPc-Cl dye under γ-ray exposure with different doses were recognized by using Fourier transform infrared spectroscopy (FTIR). The surface composition of the SubPC-Cl thin films under γ-ray exposure with different doses (0.0 & 50 kGy) was recognized by using X-ray photoelectron spectroscopy (XPS). X-ray diffraction (XRD), Field emission scanning electron microscopy (FE-SEM) and High-resolution transmission electron microscopy (HR-TEM) results were applied to determine the crystal structure and morphology of the SubPC-Cl thin films under γ-ray exposure with different doses. Various approaches such as the first derivation of the absorption spectrum fitting (DASF), Tauc's method, Drude model and the single-effective-oscillator model were discussed to obtain the optical properties of SubPc-Cl) thin films under γ-ray exposure with different doses. Such investigation can add to the growth of subphthalocyanine applications such as photovoltaic or dosimetry applications. Highlights: A spectroscopic study and the effect of gamma rays on boron subphthalocyanine dye are investigated. The structure of SubPc-Cl dye under γ-ray exposure was recognized by FTIR, XRD, XPS, FE-SEM and HR-TEM. Various approaches such as (DASF), Tauc's method, Drude model and the single-effective-oscillator model were discussed. This investigation is essential for the use of SubPC-Cl thin films in photovoltaic or dosimetry applications.